Digitization of aging-in-place: an international comparison of the value-framing of new technologies - Edward-D- Stvens; Redman-MacLarain (Al-Qanṭara, 2023)
Policymakers from all across the world are increasingly concerned about planning for ageing populations. Initiatives for "ageing in place," linked to services and care that let older people stay in their homes and communities, are essential to strategies for promoting healthy ageing. More and more, it is suggested that technological advancements, particularly the growth of digital technology, could be crucial in supporting these activities. In this study, the discursive framing of technology in aging-in-place policy documents gathered in three nations—The Netherlands, Spain, and Canada—was examined and compared using qualitative document analysis. We concentrate on how technological interventions are conceptualised in relation to values like quality of life, independence/autonomy, risk management, social inclusion, "active ageing," sustainability/efficiency of health care delivery, support for carers, etc.